4-H Weather and Climate Workshop - Clyde W. Fraisse; William R. Lusher; Melissa Griffin; Arthur A. Texeira (EDIS)
AE-447, an 11-page illustrated instructor’s guide by Clyde W. Fraisse, William R. Lusher, Melissa Griffin, and Arthur A. Texeira, provides instructors with directions, equipment lists, background resources, instructions for setup, script for the power point presentation, conducting the workshop, and follow up questions. Includes relevant Sunshine State Standards in Science, Mathematics, and Visual Arts. Published by the UF Department of Agricultural and Biological Engineering, March 2009.